RESOURCE CURSE REVISITED: CLIMATE CHANGE, ARMS PROLIFERATION, AND THE CRISIS OF GOVERNANCE IN THE GULF OF GUINEA - Acholonu, Chidozie Douglas; Abubakar, Idris (African Journal of Social and Behavioural Sciences, 2025)
The Gulf of Guinea, a strategically vital maritime region in West and Central Africa, faces compounding threats from climate change and arms proliferation that undermine its socio-economic stability. This study explores how rising sea levels, extreme weather events, and environmental degradation intersect with the spread of small arms and light weapons (SALWs) to intensify conflict, displacement, and economic decline. Through qualitative analysis of policy documents, regional reports, and case studies, the paper examines the cyclical relationship between climate change, the resource curse, and armed violence in fuelling a governance crisis. Findings reveal that climate change acts as a threat multiplier, escalating competition over dwindling fisheries and arable land, while arms proliferation empowers criminal networks and non-state actors. The study introduces the concept of a “climate-resource-conflict trap,” offering new insights into environmental security and concluding with multi-level policy recommendations for community-based adaptation, regional arms control, and climate-resilient peacebuilding.